Get to Know the Values Contained in Jepara Tatah Carving Art as Character Education - Prasetya, Arif Budi; Wijayanto, Wasis (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2024)
Introduction/Main Objectives: This research aims to recognize and understand the values contained in the art of carving, focusing on carving art in Jepara. Research Methods: This research uses a research method with a qualitative descriptive research type, data collection techniques using the results of observation, interviews and documentation. Finding/Results: This research has the meaning of ensuring that local wisdom in Jepara has a young generation that can preserve its traditions and culture or in other words (nguri-uri budoyo). So it can be used to shape the character of students at school.